2015
DOI: 10.1007/s11013-015-9469-0
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Notions on Violence and PTSD in the Military: Institutional and Personal Narratives of Combat-Related Illness

Abstract: Research indicates that soldiers struggling with PTSD under-utilize mental health care. Quantitative studies of barriers to care point to the importance of soldiers' beliefs about mental health and mental health interventions in their care-seeking behavior, yet these studies still struggle to understand the particular beliefs involved and the ways they impact care-seeking behavior. This preliminary study makes a start in examining these questions through qualitative literature analysis. It maps out dominant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(77 citation statements)
references
References 46 publications
0
77
0
Order By: Relevance
“…Adherence to traditional masculine behaviours has been negatively associated with helpseeking behaviours (Garcia et al, 2011;Lane & Addis 2005;Berger, Levant, McMillan, Kelleher & Sellers, 2005). With the military fostering greater adherence to these norms, it is vital that the effect of these norms be studied in relation to health-seeking behaviours, namely because Western soldiers underutilize mental health care (Molendijk, Kramer and Verweij, 2016;Hoge et al, 2004;Kim et al, 2010). According to Berger et al (2005), civilian men "who score higher on measures of gender role conflict and traditional masculine ideology tend to have more negative attitudes toward psychological help seeking" (p. 63).…”
Section: Masculinitymentioning
confidence: 99%
See 4 more Smart Citations
“…Adherence to traditional masculine behaviours has been negatively associated with helpseeking behaviours (Garcia et al, 2011;Lane & Addis 2005;Berger, Levant, McMillan, Kelleher & Sellers, 2005). With the military fostering greater adherence to these norms, it is vital that the effect of these norms be studied in relation to health-seeking behaviours, namely because Western soldiers underutilize mental health care (Molendijk, Kramer and Verweij, 2016;Hoge et al, 2004;Kim et al, 2010). According to Berger et al (2005), civilian men "who score higher on measures of gender role conflict and traditional masculine ideology tend to have more negative attitudes toward psychological help seeking" (p. 63).…”
Section: Masculinitymentioning
confidence: 99%
“…It is an evident trend in Western society for soldiers with PTSD to underutilize health care ( Molendijk, Kramer and Verweij, 2016;Hoge et al, 2004;Kim et al, 2010). Hoge et al (2004) found that between 23 to 40 percent of active duty soldiers with a mental health issue sought professional care within the span of a year (Hoge et al, 2004).…”
Section: Barriers To Carementioning
confidence: 99%
See 3 more Smart Citations